ALOKASI DAN PERSEPSI PEMANFAATAN KREDIT USAHA RAKYAT (KUR) OLEH PETERNAK AYAM RAS PETELUR PADA BANK RAKYAT INDONESIA (BRI) UNIT AMPARITA KABUPATEN SIDENRENG RAPPANG - Nurul Azhima Trisuci; Ahmad R. Siregar; Syahdar Baba (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT. The purpose of this study to determine the number of allocations People's Business Credit ( KUR ) By Broiler Breeder Laying on Bank Rakyat Indonesia ( BRI ) Unit Amparita Sidenreng Rappang for farm business , and to determine the perception of farmers on Public Credit utilization by laying chicken breeder Bank Rakyat Indonesia Unit Amparita Sidenreng Rappang . This research was carried out during this study was conducted from June to July 2013, in the villages in the area of Bank Rakyat Indonesia (BRI) Unit Amparita Sidenreng Rappang, namely: Village Tanete, Allakkuang Village, Village Takkalasi, Arateng village, village Pulu Toddang, Village Amparita, Teteaji Village, Village Polewali, Pajalele Village, Village Baula, Massepe Village, and the Village Teppo in Sidenreng Rappang. This research is descriptive quantitative research, which is a type of research that describes or depicts a study phenomena such or discuss the relationship between the variables without seeing one another variable, the variable in this study was the effectiveness of the utilization of the People's Business Credit (KUR) by a chicken farmer laying on the People's Bank Amparta Unit, Sidenreng Rappang. Most of the farmers use chicken laying Public Credit as venture capital, although there are someamong breeders use to kosumtif , The higher number of Public Credit obtained eat the more the farmers who use it for business capital , the level of effectiveness of Public Credit utilization by farmers chicken laying on Bank Rakyat Indonesia unit Amparita Effective means Sidenreng is mostly laying chicken farmers use small loans for farm business development as expected by the Bank , the level of perception of the use of business credit with Bank Rakyat Indonesia unit Amparita by broiler breeder laying with a score of 616.Based on the basic assumption of class intervals and class range, with a score of Effective category which is in the interval ( 549.8 to 679.4 .